The origins of early Christian literature: contextualizing the New Testament within Greco-Roman literary culture - Walsh, Robyn Faith (Cambridge University Press, 2021)
The Myth of Christian Origins -- The Romantic "Big Bang": German Romanticism and Inherited Methodology -- Authorship in Antiquity: Specialization & Social Formations -- Redescribing Early Christian Literature: The Gospels, The Satyrica, and Anonymous Sources -- The Gospels as Subversive Biography -- Conclusion.